2017
DOI: 10.1007/s11596-017-1776-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis performance of 99mTc-MIBI and multimodality imaging for hyperparathyroidism

Abstract: This study aimed to examine the diagnosis performance of Tc-methoxyisobutylisonitrisonitrile (Tc-MIBI) and multimodality imaging [ultrasound, single-photon emission computed tomography/computed tomography (SPECT/CT)] for hyperparathyroidism (HPT). From Nov. 2009 to Dec. 2015, clinical data of a total of 43 HPT patients (16 males and 27 females; 26-70 years old, average age: 51.60±10.66 years old) were retrospectively analyzed. Among them, 19 patients with primary hyperparathyroidism (PHPT) underwent Tc-MIBI pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…Li et al [11] reported that 8.05 mm was the optimal cut-off value in lesions diameter for predicting 99m Tc-MIBI SPECT/CT positive in SHPT. Zhou et al [24] reported that the average maximum diameter of 99m Tc-MIBI SPECT/CT positive lesions was 19.6 ± 9.5 mm in hyperparathyroidism. NMDG refered to true positive lesions, while MIBI positive included ture positive and false positive lesions.…”
Section: Discussion 99mmentioning
confidence: 99%
“…Li et al [11] reported that 8.05 mm was the optimal cut-off value in lesions diameter for predicting 99m Tc-MIBI SPECT/CT positive in SHPT. Zhou et al [24] reported that the average maximum diameter of 99m Tc-MIBI SPECT/CT positive lesions was 19.6 ± 9.5 mm in hyperparathyroidism. NMDG refered to true positive lesions, while MIBI positive included ture positive and false positive lesions.…”
Section: Discussion 99mmentioning
confidence: 99%
“…When combined with singlephoton emission computed tomography/computed tomography (SPECT/CT), functional and anatomical, the sensitivity of scintigraphy is increased. Multiple studies have reported that dual-phase 99m Tc-MIBI scintigraphy is superior to US, especially when combined with SPECT/CT, in patients with HPT [12][13][14], but these studies did not distinguish SHPT from PHPT for statistical analysis. For PHPT, several investigations have reported that 99m Tc-MIBI SPECT/CT is superior to dual-phase 99m Tc-MIBI scintigraphy [11,15,16].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…The image was considered positive on visual analysis when it met one of the following criteria: (1) abnormal 99m Tc-MIBI uptake was observed on both early and delayed imaging; (2) abnormal 99m Tc-MIBI uptake was observed on either early or delayed imaging. The image was considered negative when abnormal 99m Tc-MIBI uptake was observed on neither early nor delayed imaging [13].…”
Section: Image Analysis Dual-phase 99m Tc-mibi Scintigraphymentioning
confidence: 99%
“…Different from the above anatomical imaging, technetium-99m methoxyisobutylisonitrile ( 99m Tc-MIBI) scintigraphy is a functional exploration and regarded as the best preoperative localizing method for patients with PHPT or SHPT [6] and when combined with single photon emission computed photography/ computed photography (SPECT/CT), functional and anatomical, the sensitivity of scintigraphy can be able to increase. Multiple studies have reported 99m Tc-MIBI scintigraphy superior to US especially combined with SPECT/CT in patient with hyperparathyroidism [13][14][15], but these studies do not separate SHPT from primary hyperparathyroidism (PHPT) for statistics and analysis. For PHPT, several investigations had reported 99m Tc-MIBI SPECT/CT superior to scintigraphy [16][17][18], although the other study did not find SPECT/CT superior to scintigraphy [19].…”
Section: Introductionmentioning
confidence: 99%